A different pond [book with audioplayer] - Phi, Bao, 1975- (VOX Books, 2019)
"As a young boy, Bao Phi awoke early, hours before his father's long workday began, to fish on the shores of a small pond in Minneapolis. Unlike many other anglers, Bao and his father fished for food, not recreation. Between hope-filled casts, Bao's father told him about a different pond in their homeland of Vietnam"--